2022
DOI: 10.1530/joe-21-0358
|View full text |Cite
|
Sign up to set email alerts
|

100 YEARS OF INSULIN: Pancreas pathology in type 1 diabetes: an evolving story

Abstract: We review the current knowledge of pancreas pathology in type 1 diabetes. During the last two decades dedicated efforts towards the recovery of pancreas from deceased patients with type 1 diabetes have promoted significant advances in the characterization of the pathological changes associated with this condition. The implementation autoantibody screening among organ donors has also allowed examining pancreas pathology in the absence of clinical disease, but in the presence of serological markers of autoimmuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 106 publications
(143 reference statements)
0
37
0
1
Order By: Relevance
“…Particularly, with the coronavirus pandemic and in its aftermath, there might be a further increase in diabetes mellitus, including T1DM. We and others have shown that the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infects cells of both the endocrine and exocrine pancreas, which might lead to necroptotic cell death 5 , as previously observed for enteroviruses 4 . The Centers for Disease Control and Prevention ( CDC ) have reported an increased risk of new-onset diabetes mellitus in children and adolescents after having COVID-19.…”
Section: Why Is Islet Restoration Important Now?mentioning
confidence: 77%
See 1 more Smart Citation
“…Particularly, with the coronavirus pandemic and in its aftermath, there might be a further increase in diabetes mellitus, including T1DM. We and others have shown that the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infects cells of both the endocrine and exocrine pancreas, which might lead to necroptotic cell death 5 , as previously observed for enteroviruses 4 . The Centers for Disease Control and Prevention ( CDC ) have reported an increased risk of new-onset diabetes mellitus in children and adolescents after having COVID-19.…”
Section: Why Is Islet Restoration Important Now?mentioning
confidence: 77%
“…Adding to the need for regenerative therapies, the incidence of T1DM is also rapidly increasing worldwide, reflecting the increasing role of environmental factors over genetic factors 4 . Particularly, with the coronavirus pandemic and in its aftermath, there might be a further increase in diabetes mellitus, including T1DM.…”
Section: Why Is Islet Restoration Important Now?mentioning
confidence: 99%
“…T1D is an autoreactive disease arising from immune destruction of insulin-producing pancreatic β cells ( 359 ). Both NEU1 and NEU3 have been implicated in the pathogenesis of T1D.…”
Section: Neus and Mucs In Autoimmune Diseasesmentioning
confidence: 99%
“…T1D patients donating tissues for research helped to collect a significant evidence that T1D pathogenesis can follow different individual scenarios but also that mechanisms described in animal models are not all or not just as strongly present in the human immune system. For example, the infiltration of immune cells around the islet of Langerhans, designated as insulitis, in which activated CD4+ T cells control macrophages to induce killing of the β-cells by cytokines and reactive oxygen species, is clearly evident in mice ( 23 ) but not evident in human pancreas ( 24 , 25 ). Cytotoxic CD8+ T cells are essential for the ultimate destruction of β-cells, while their antigen specificity varies between patients ( 4 , 26 ).…”
Section: Immunopathogenesis Of T1d How Much Do We Actually Know?mentioning
confidence: 99%